2020
DOI: 10.1515/mgmc-2020-0002
|View full text |Cite
|
Sign up to set email alerts
|

An accelerated and effective synthesis of zinc borate from zinc sulfate using sonochemistry

Abstract: Recently, sonochemistry has been used for the synthesis of inorganic compounds, such as zinc borates. In this study using zinc sulphate heptahydrate (ZnSO4·7H2O) and boric acid (H3BO3) as starting materials, a zinc borate compound in the form of Zn3B6O12·3.5H2O was synthesized using an ultrasonic probe. Product’s characterization was carried out with using X-ray diffraction (XRD), Scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FT-IR) and Raman spectroscopy. Zinc borate compound’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The TG curves of the samples in Figure 7 showed two steps of mass decrease as tabulated in Table 3 [40]. Even if the submicron particles obtained in the present study was not pure zinc borate, they can be easily dispersed in mineral oil to increase the lubrication efficiency of the mineral oil for reduction of wear of metal parts as in the study of Savrik et al [26].…”
Section: Thermal Analysis Of the Samplesmentioning
confidence: 55%
“…The TG curves of the samples in Figure 7 showed two steps of mass decrease as tabulated in Table 3 [40]. Even if the submicron particles obtained in the present study was not pure zinc borate, they can be easily dispersed in mineral oil to increase the lubrication efficiency of the mineral oil for reduction of wear of metal parts as in the study of Savrik et al [26].…”
Section: Thermal Analysis Of the Samplesmentioning
confidence: 55%
“…The C−H bending vibration peak shifted from 1350 to 1353 cm −1 suggests that the interaction between sodium borate and CH 3 promoted B−O−H or B−O−C bonding, as observed in previous studies. 26,27 We also confirm the chemical interaction between PMMA/Borax and perovskite via high-resolution Xray photoelectron spectroscopy (XPS) to determine whether any changes occurred in the electronic states of the perovskite. Figure 1e shows that the distinctive binding energies (BE) of 142.4 and 138.1 eV for the Pb 4f 5/2 and 4f 7/2 orbitals are shifted to 144.1 and 139.1 eV, corresponding to coordinated Pb in the perovskite crystal.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
“…In addition, the B-O bonding peak at 1510 cm À1 became stronger and the C-H bending vibration peak was shied from 1352 cm À1 to 1373 cm À1 with increasing borax concentrations, indicating that B-O-H or B-O-C bonding is promoted by the interaction between sodium borate and CH 3 . [25][26][27][28] Our previous study using proton nuclear magnetic resonance indicated that the presence of PMMA in the perovskite leads to the formation of hydrogen bonds between PMMA and the perovskite. 22 Specically, the interaction between the dipole moment of MA + (CH 3 NH 3 + ) in the perovskite and the polar C]O bond in PMMA promoted hydrogen bond formation.…”
Section: Resultsmentioning
confidence: 99%